Cytological characteristics of histological types of lung cancer by cytomorphometric and flow cytometric analyses using liquid‐based cytology materials. Issue 6 (28th February 2023) - Tanaka, Ryota; Fujiwara, Masachika; Sakamoto, Norihiko; Kanno, Hitomi; Arai, Nobuaki; Tachibana, Keisei; Kishimoto, Koji; Anraku, Masaki; Shibahara, Junji; Kondo, Haruhiko
Abstract: Background: Distinguishing the histological types of lung cancer is essential for determining treatment strategies in clinical practice. In this study, cytomorphological characteristics and proliferative activities were compared among histological types of lung cancer by cytomorphometric and flow cytometric analyses using liquid‐based cytology (LBC) samples. Methods: Scraped LBC samples from 73 surgically resected specimens were collected between August 2018 and November 2019. Papanicolaou‐stained and paired Ki‐67‐stained slides were used for cytomorphometric analyses. Another sample for each case was analyzed using a flow cytometric system (LC‐1000). The cell proliferation index (CPIx) was calculated to evaluate proliferative activity. Results: In total, 73 cases, including cases of adenocarcinoma ( n  = 53), squamous cell carcinoma ( n  = 14), small cell carcinoma ( n  = 1), large cell neuroendocrine carcinoma (NEC; n  = 3), and pleomorphic carcinoma ( n  = 2) were evaluated. Small cell carcinoma and large cell NEC were categorized into a single group, NEC. The adenocarcinoma group tended to have a larger nuclear area and longer perimeter than other histological types. The NEC group had a considerably higher Ki‐67 labeling index and significantly higher CPIx than other histological types ( p  = .030). A significant positive correlation was observed between the Ki‐67 labeling index and CPIx for all cases ( r  = 0.362, p  = .002). Conclusion: The Ki‐67 labeling index and flow cytometric analyses focus on proliferative activity for the distinction of histological types of lung cancer, thereby guiding clinical decision‐making.